Examining the Relationship Between Gender, Science Learning Experiences and Science Performance in Indonesia - Alfatih, Ainun Najib; Syam, Sriwidayani (Indonesian Journal of Educational Studies, 2025)
This study investigates the influence of science learning experiences on students’ science performance in Indonesia, utilizing data from PISA 2015 assessment. Science learning experiences refer to students’ engagement in different science subjects, including Physics, Chemistry, Biology, Earth and Space Science, Applied Science, and Integrated Science. A quantitative approach was employed using multiple statistical analyses, including descriptive analysis, independent t-test, and regression analysis. The findings indicate that students who enrolled in specific science subjects such as Physics, Chemistry, and Biology exhibited higher science performance compared to those who did not. However, inconsistent results were found for Applied Science and Integrated Science. These findings suggest that the type and structure of science education play a critical role in students’ academic achievement. The study highlights the need for curriculum improvements to enhance science learning experiences in Indonesian Schools.